(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
The biometric and morphological characters of Macroporella retica Zanin Buri 1965 from the type-locality (Aviatico - Lombardy) are described. On the basis of these observations, it has been possible to confirm that Macroporella retica represents a junior synonym of Griphoporella curvata, as stated by Barattolo et al. (1993).